2009
DOI: 10.1158/0008-5472.sabcs-09-1013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Sentinel Lymph Node Biopsy in Clinically Node Negative Patients after Neoadjuvant Chemotherapy for Breast Cancer – A Systematic Review and Metaanalysis.

Abstract: BackgroundThe sentinel lymph node biopsy (SLNB) has become an accepted alternative to the axillary lymph node dissection (ALND) for pathologic evaluation of the axillary lymph node status in patients with early breast cancer and a clinically negative axilla. Patients with a negative sentinel lymph node are spared the ALND and its associated morbidities.Currently, there is insufficient evidence to recommend the use of SLNB in patients who have received neoadjuvant chemotherapy (NAC), and treatment of the axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Various studies reported that the SLN identification rate after neo-adjuvant chemotherapy was over 90% while the false-negative rate was almost 10% (30,31). Regardless of the present data, there is concern on the hypothesis that SLN biopsy after neo-adjuvant chemotherapy might increase the number of the false-negative biopsies due to multiple factors such as fibrosis, distorted lymphatic drainage, tissue scarring and not always uniform response of the patients to treatment (32). The definition of the oncologic stage and the lymph node status before the neo-adjuvant chemotherapy seems to be essential for the final prognosis and the major advantage of the SLN biopsy.…”
Section: Discussioncontrasting
confidence: 57%
“…Various studies reported that the SLN identification rate after neo-adjuvant chemotherapy was over 90% while the false-negative rate was almost 10% (30,31). Regardless of the present data, there is concern on the hypothesis that SLN biopsy after neo-adjuvant chemotherapy might increase the number of the false-negative biopsies due to multiple factors such as fibrosis, distorted lymphatic drainage, tissue scarring and not always uniform response of the patients to treatment (32). The definition of the oncologic stage and the lymph node status before the neo-adjuvant chemotherapy seems to be essential for the final prognosis and the major advantage of the SLN biopsy.…”
Section: Discussioncontrasting
confidence: 57%
“…To date, 4 metaanalyses that access the accuracy of SLNB after neoadjuvant chemotherapy have been published [24][25][26][27]. Although most of the included studies are limited by small size, retrospective design, and wide variation in results, the sentinel identification rates and false-negative rates determined were similar to those seen in patients undergoing SLNB before chemotherapy [28].…”
Section: Timing Of Axillary Procedures In the Neoadjuvant Settingmentioning
confidence: 99%
“…Data supporting this approach is limited to several large retrospective series and meta-analyses, while SNB before nCT is considered to be standard of care [12].…”
Section: Introductionmentioning
confidence: 99%